2003
DOI: 10.1038/sj.jp.7210877
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Macrosomia (≥4500 g): Perinatal Outcome of 231 Cases According to the Mode of Delivery

Abstract: Vaginal delivery is achievable in 88.9% of pregnancies with infants >or = 4500 g allowed to labor, at the expense of a 7.7% risk of perinatal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
3
21
0
3
Order By: Relevance
“…1 Schaefer-Graf et al 13 in their study found that hypoglycaemia was associated with only 1.5% of perinatal birth asphyxia at 5 minutes. The higher number in our study could be because of the small sample size of 106 in comparision to 887 in the study conducted by Schaefer-Graf et al 13 Hypocalcemia was observed in 5 LGA babies in the present study out of which 3 had hypoglycemia (p=.004). Hypocalcemia as such may not cause hypoglycemia but whenever hypoglycemia is documented in LGA baby of non-diabetic mother, the presence of concomitant hypocalcemia should be considered especially when hypocalcaemic symptoms are not relieved by treatment with intravenous dextrose fluid.…”
mentioning
confidence: 36%
See 1 more Smart Citation
“…1 Schaefer-Graf et al 13 in their study found that hypoglycaemia was associated with only 1.5% of perinatal birth asphyxia at 5 minutes. The higher number in our study could be because of the small sample size of 106 in comparision to 887 in the study conducted by Schaefer-Graf et al 13 Hypocalcemia was observed in 5 LGA babies in the present study out of which 3 had hypoglycemia (p=.004). Hypocalcemia as such may not cause hypoglycemia but whenever hypoglycemia is documented in LGA baby of non-diabetic mother, the presence of concomitant hypocalcemia should be considered especially when hypocalcaemic symptoms are not relieved by treatment with intravenous dextrose fluid.…”
mentioning
confidence: 36%
“…3,4 LGA babies are at risk of many complications such as difficult delivery, neonatal injuries and metabolic complications like hyperbilirubinemia, hypoglycemia, hypocalcemia, polycythemia etc. 5,6 During intrauterine life, transplacental transport supplies various nutrients including glucose, which is the most important fetal energy substrate to the growing fetus. With the abrupt cessation of maternal supply of glucose immediately after birth, transient hypoglycaemia is common in LGA infants because of the physiologic immaturity of pathways of glucose homeostasis and glucose values reach a nadir at 2-3 hours of life.…”
Section: Introductionmentioning
confidence: 99%
“…Os vários estudos existentes na literatura não são específicos em seus critérios de inclusão/exclusão [6][7][8] . Entretanto, grande parte deles apontam a forte associação entre a MF e a interrupção da gestação pela via alta 13,18,20,[24][25][26] . Dentre os estudos citados, o percentual de partos cesáreos variou de 27,3%, em casos de fetos com peso igual ou superior a 4.500 g, a 34% para fetos com peso superior a 4.000 g 17,21 .…”
Section: Idade Paridadeunclassified
“…Increased risks of maternal obstetrical complications and longer labor periods especially in primigravid women have been reported in mothers of macrosomic babies [5]. Consequently, fetal macrosomia is a risk factor for fetal injury and maternal morbidity in type I, type II, and gestational diabetic pregnancies [1,4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%